Developments, Evolution, and Implications of National Diagnostic Criteria for COVID-19 in China - Ma, Lin-Lu; Li, Bui-Hui; Jin, Ying-Hui; Deng, Tong; Ren, Xue-Qun; Zeng, Xian-Tao (Frontiers in Medicine, 2020)
Recently WHO has characterized COVID-19 as a pandemic: to diagnose it accurately, decrease misdiagnosis and missed diagnoses is very important for management. Therefore, we have analysed the seven versions of China’s national guidelines to examine how the diagnostic criteria roadmap has developed and evolved, in order to share our experience worldwide. In this article, we present the developments from the first to seventh versions, involving changes of case classification, changes to ‘suspected case’, changes in ‘confirmed case’, changes in clinical classifications, changes in ‘severe case’, and unchanged criteria. We have also discussed the reasons and implications for these changes, and are looking forward to providing suggestions for worldwide understanding and management of this pandemic. Nucleic acid test is currently accepted as the gold standard method to confirm diagnosis. In addition, imaging examination and epidemiological history should also be considered as auxiliary diagnosis methods.